The complete mitochondrial genome of the Japanese threadfin bream, Nemipterus japonicus (Teleostei, Nemipteridae). (2nd January 2016) - Li, Yinglei; Chen, Jianhua; Yan, Binlun; Meng, Xueping
Abstract: The complete mitochondrial sequence of the Japanese threadfin bream, Nemipterus japonicus has been determined. The circle genome is 16, 995 bp in size, and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a control region. The gene order and composition of N. japonicus was similar to that of most other teleosts. The base composition of H-strand is 28.11% (A), 28.02% (T), 16.64 % (G) and 27.24 % (C), with an AT content of 56.12%. All genes are encoded on the heavy strand with the exception of ND6 and eight tRNA genes. The mitochondrial genome of N. japonicus presented will be in favor of resolving phylogenetic relationships within the family Nemipteridae and the Perciformes.